ANALISIS SISTEM PEMBAYARAN NON TUNAI MENGGUNAKAN E-MONEY PADA NIAT PEMBELIAN - Herlin; Yanto Effendi; Kiemas Kurniawan (Universitas Muhammadiyah Bengkulu, 2023)
Payments for increasingly sophisticated sales system transactions have an impact on the ease of consumer transactions, both using cash and non-cash payments. In conducting consumer payment transactions. Currently, consumers who have a high level of routine prefer to use E-Money in their transactions. This is because it is safer and more efficient and provides convenience for consumers in transacting.Payments Using Credit Cards have a negative effect on consumers' buying intentions at Bencoolen Mall Bengkulu, while Payments Using OVO Cash and Shopee Pay have a positive effect on consumers' buying intentions at Bencoolen Mall Bengkulu. Taken together, payments using credit cards, OVO cash and Shopee Pay have a positive effect against the consumer's desire to buy at Bengcoolen Mall Bengkulu